Kompil II a study of civil society's political engagements - Velasco, Djorina R. (Philippine Sociological Review, 2004)
This article presents a case study of the Kongreso ng Mamamayan Pilipino II (or Kompil II for short), a civil society formation active in the extra-parliamentary ouster of Philippine President Joseph Ejercito Estrada over charges of grave corruption and abuse of power in January 2001. The study illustrates the highly politicized nature of many Philippine civil society organizations (CSOs). It shows how the Kompil II coalition flexed its political muscle through mass actions, agenda building and alliance work. The research also demonstrates that although Kompil II members were united in their opposition to Estrada, their unity was sutured along two critical lines: (1) whether civil society leaders shall accept government positions and (2) whether CSOs shall endorse or campaign for political aspirants. Divergent outlooks among member organizations, thus, indicate the heterogeneous nature of Philippine civil society. The study concludes that in a political system such as in the Philippines - where political parties are weak and vested elite interests dominate formal politics - more vibrant and transformative political activity is possible outside the institutional shell of electoral politics, in civil society gatherings and in the 'parliament of the streets'